Settlement Frequency Stress on Testis and the Protective Effect of Oleuropein in Japanese Quails - Gungor, Ibrahim Halil; Celik, Ebru; Bahsi, Muammer; Karakoc, Sirvan; Turk, Gaffari; Ciftci, Mehmet; Sonmez, Mustafa (Aves, 2025)
The cohabitation of poultry animals is considered a settlement frequency, and this density creates a stress factor that negatively affects sexual performance. In this study, the stress caused by settlement frequency on the testis and the protective effect of oleuropein, an olive leaf extract, were investigated. For this purpose, 90 Japanese quails were divided into two groups based on their body weights. In the first group, quails were kept under normal conditions with 12 quails per cage. In the second group, stress was induced by increasing the settlement frequency to 18 quails per cage. Both groups were further divided into three subgroups, and experimental groups were formed by adding 0, 200, and 400 ppm oleuropein to their diets. At the end of the study, 6 quails from each group (36 in total) with body weights close to the group average were slaughtered using the cervical dislocation method. The study analyzed fatty acids in blood serum after slaughter and determined average testicular weight, Gonado-Somatic-Index, testicular spermatid, and sperm counts. The stress factor was found to significantly decrease spermatid and sperm counts compared to the control group. However, the addition of 200 and 400 ppm oleuropein to the stress groups prevented this decrease. The spermatid count in the 400 ppm oleuropein group, which was not exposed to stress, was significantly higher than that of the control group. While no effect of the stress factor on fatty acids was observed, significant differences in fatty acids were found in the oleuropein-supplemented groups and in the combined stress and oleuropein groups. In conclusion, 200-400 ppm oleuropein supplementation to the diets of Japanese quails was beneficial in improving the decreased testicular exocrine function caused by settlement frequency stress.
Keywords: Fatty acids; quail; settlement frequency; stress; testis